Verb-Verb Construction in Bugis Language: A Linguistic Typology Approach - Alien Kurnia Warya Selia; Achmad Dicky Romadhan (Masyarakat Linguistik Indonesia Universitas Andalas, 2024)
This study examines the formation of serial verbs in the Bugis Bone language utilizing a qualitative descriptive approach and typological analysis. Data were collected by observation, including audio recordings of Bugis speakers’ direct talk, and supplemented by interviews for contextual comprehension. The assessment focused on language structures, and identifying patterns and distributions of lexemes and phrases. The results demonstrate that Bugis serial verbs align with the worldwide typology of serial verbs, consisting of four syntactic categories and six semantic categories: movement, directional, manner, cause-effect, comitative, modality, and aspect. This work is significant for its contribution to linguistic typology, providing insights into the universal elements of serial verb formations and the distinct qualities of the Bugis Bone language. The results have ramifications for the comprehensive understanding of Austronesian languages, establishing a basis for comparative analyses and contributing to the preservation of linguistic variety. Moreover, the study enhances understanding of the functioning of serial verb formulations within a particular linguistic and cultural framework, hence advancing theoretical knowledge in syntax and semantics. Future research may explore Bugis sentence forms through other theoretical frameworks to enhance the understanding of Bugis language typology.